Drug-like property-driven optimization of 4-substituted 1, 5-diarylanilines as potent HIV-1 non-nucleoside reverse transcriptase inhibitors against rilpivirine-resistant mutant virus. Issue 12 (15th June 2017) - Wei, Lei; Wang, Hui-Ling; Huang, Li; Chen, Chin-Ho; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung; Xie, Lan
Graphical abstract: Abstract: On the basis of our prior structure-activity relationship (SAR) results, our current lead optimization of 1, 5-diarylanilines (DAANs) focused on the 4-substituent (R 1 ) on the central phenyl ring as a modifiable position related simultaneously to improved drug resistance profiles and drug-like properties. Newly synthesized p -cyanovinyl-DAANs (8a –8g ) with different R 1 side chains plus prior active p -cyanoethyl-DAANs (4a –4c ) were evaluated not only for anti-HIV potency against both wild-type HIV virus and rilpivirine-resistant (E138K, E138K+M184I) viral replication, but also for multiple drug-like properties, including aqueous solubility, lipophilicity, and metabolic stability in human liver microsomes and human plasma. This study revealed that both ester and amide R 1 substituents led to low nanomolar anti-HIV potency against wild-type and rilpivirine-resistant viral strains (E138K-resistance fold changes < 3). The N -substituted amide-R 1 side chains were superior to ester-R 1 likely due to improved aqueous solubility, lipophilicity, and higher metabolic stability in vitro . Thus, three amide-DAANs8e, 4a, and4b were identified with high potency against wild-type and rilpivirine-resistant viral strains and multiple desirable drug-like properties.